Enhancement of English Speaking Skills Through Role Play Technique - Khulimuli, Shiva Bahadur (Bagiswori Journal, 2022)
This study aims to investigate about how students’ English speaking skills can be enhanced through the employment of role play technique. The sample population of the study was taken from the grade XI students of Bagiswori Secondary School. The experimental group was taught through role play technique while the control class was taught through the traditional grammar based techniques. The total population of this study was 30 students who were enrolled in the academic year 2020/2021. It was experimental study. The tools applied in this research were observation sheet and speaking test. After 15 lessons of the teaching, the post-test of speaking was conducted in which the students in both groups were asked to answer. The results revealed that the experimental group’s motivation has been enhanced and has improved English speaking skill significantly.